Hubungan Antara Tingkat Religiusitas dengan Penyesuaian Diri Mahasiswa Baru Fakultas Kedokteran Universitas Muhammadiyah Semarang - Putri Novi Kurniasari; Noor Yazid; Rochman Basuki (Jurnal Anestesi, 2025)
Adjustment is a process that includes mental and behavioral responses, which is an individual's attempt to successfully overcome the conflicts and frustrations that are experienced within him. Adjustment is a common problem encountered in new students and is influenced by several factors, one of which is religiosity. Religiosity is a person's belief and experience regarding the religion he embraces. Religiosity is considered formal and institutional because it reflects a commitment to beliefs and practices according to certain (religious) traditions. Self-adjustment includes academic, social, personal-emotional adjustments, and institutional attachments. Purpose To find out whether there is a relationship between the level of religiosity and the adjustment of new students at the Faculty of Medicine, University of Muhammadiyah Semarang. Research Methods: This analytic study with a cross-sectional approach used a population of 141 respondents at the UNIMUS Faculty of Medicine. The independent variable is religiosity- and the dependent variable is adjustment. Data analysis used the Spearman rank test with a 95% confidence level. Research Results: The relationship between religiosity and self-adjustment with a correlation coefficient of 0.504 and a p-value of 0.000. Conclusion: There is a significant unidirectional relationship between the level of religiosity and the adjustment of new students at the UNIMUS Faculty of Medicine.